Analysis Of The Importance Gender Equality In The “Kartini” Movie By Hanung Bramantyo - Delfina Fatihayah; Marudut Bernadtua Simanjuntak (LITERACY : International Scientific Journals of Social, Education, Humanities, 2022)
This film is based on a true story about the hero of Indonesian women's emancipation named Kartini who was given the noble title of Raden Ajeng Kartini. Kartini grew up watching her mother, Ngashira, become an outcast and considered a maid because she had no royal blood. Kartini fought for the right to education for everyone, especially women. This film is a journey of Kartini, a character who struggles against tradition and even her family to fight for the equal rights of all Indonesian people. From film Raden Ajeng Kartini, the researcher aims to analyze the importance of gender equality in Indonesian society at that time. The use of the method applied in the analysis of the Kartini film is a qualitative method, the researcher chose the qualitative method because it focuses more on the historical process and meaning of this film. In the past, Indonesian people were very thick with Indonesian Javanese culture, so residents had to obey these rules, otherwise it would be considered strange. Therefore, this study concludes that the end result is that gender equality is very important for the social environment, women can also become successful and independent people without leaving customs and culture.